Validation of Two-Minute Step Test and Development of VO Prediction Equation in Older Korean Adults - Soyoung Park; Jungjun Lim; On Lee (Korea Institute of Sport Science, 2023)
PURPOSE This study aimed to verify the criterion validity of the two-minute step test in older Korean adults, develop an equation for predicting VO2max, and verify cross-validation. METHODS A submaximal exercise test and the two-minute walk test were performed on 150 older adults (74 males and 74 females) aged 65 years or older. Correlation analysis was performed to confirm criterion validity. An equation for estimating VO2max was developed through multiple regression analysis, and cross-validation was confirmed by performing a correlation analysis between measured and predicted values of VO2max. RESULTS The correlation coefficient between VO2max and the two-minute step test was 0.457 (p<.001). The adjusted R2 of the developed VO2max prediction equation was 0.430 (p<.001), and the explanatory variables finally selected were sex, age, number of steps in the two-minute step test, and percentage of body fat. The correlation coefficient between the measured VO2max (19.08±4.36) and the predicted VO2max (19.73±3.36) was 0.654 (p<.001). CONCLUSIONS This study confirmed the criterion validity of the two-minute step test in older Korean adults, and the cross-validation of the developed VO2max prediction formula was verified. The explanatory variables of the prediction equation will be easy to apply in the field, and more meaningful results will be derived if the validity of the prediction equation developed for a larger number of participants is verified.